Preoperative 1-week diet can markedly decrease blood loss during hepatectomy - Kinoshita, Koichi; Beppu, Toru; Sato, Nobutaka; Akahoshi, Shinichi; Yuki, Hideaki; Yoshida, Yasushi (Translational Gastroenterology and Hepatology, 2019)
Great effort has been paid to decrease blood loss during hepatectomy. Excessive blood loss and/or allogeneic blood transfusion can cause an increased risk of perioperative morbidity and mortality and may lead to a greater risk of early tumor recurrence (1-4). Hepatic steatosis or steatohepatitis is present in 30–50% of patients in the Western countries and can increase blood loss and morbidity in patients undergoing hepatectomy for colorectal liver metastases (5-7). Steatotic livers are hypertrophic and delicate and are therefore more difficult to mobilize or transect compared to nonsteatotic livers.